Anion-enhanced solvophobic effects in organic solvent. Issue 61 (13th July 2018) - Maier, Josef M.; Li, Ping; Ritchey, Jackson S.; Yehl, Christopher J.; Shimizu, Ken D.
Abstract : Molecular balanced measured a two-fold anion-induced enhancement of the solvophobic effect in organic solvents. Abstract : The influence of salts on the solvophobic interactions of two non-polar surfaces in organic solvent was examined using a series of molecular balances. Specific anion effects were observed that followed the Hofmeister series and enhanced the solvophobic effect up to two-fold.